Efficiency In Food Grains Production In India Using DEA And SFA - Rajani Neeraj Mathur; Swati Raju Ramnath (The Central European Review of Economics and Management (CEREM), 2018)
Aim: Food security is a multi-dimensional issue and is concerned with aspects such as availability, access and utilisation. It would require major interventions that will transform the current patterns and practices of food production, distribution and consumption. Food security can be attained by increasing the level of agricultural productivity and efficiency and improvements in agricultural efficiency are at the core of the quest for food security. This paper seeks to examine the efficiency in food grains production in India for the period 1960-61 to 2013-14.~Design / Research methods: The key idea is to employ the non-parametric Data Envelopment Analysis and the parametric Stochastic Frontier Analysis to measure the efficiency of food grains production in India. We have estimated an input oriented single output, multi - input DEA models (CRS - DEA and VRS- DEA) of agricultural production to measure the efficiency in food grains production for two time periods 1960-61 to 1989-90 and 1991-92 to 2013-14. The analysis of super efficiency was conducted for both these time periods helped identify the years in which food grains production was most efficient.~Conclusions / findings: We find high average efficiency in farming operations for both the frontier methods. However, the range of efficiency obtained varies considerably for the different frontier methods. The period after 1990 has witnessed improved agricultural performance as can be inferred from the frequency distribution of the efficiency scores which indicates that during this period the overall efficiency scores have been higher and there was not a single year in which the efficiency levels have been less than 0.9. The analysis of super efficiency also vindicates the improved performance of the agricultural sector in the post 1990 periods as greater number of years recorded an efficiency score greater than 1 as compared to the previous period. However, the super efficiency scores recorded in the period 1961-1990 were higher than those in the post 1990 years suggesting thereby that there could be a tapering of the positive impact of the Green Revolution. Efficiency estimates obtained by the SFA model are marginally lower than that of the DEA model and the results of the SFA model indicate net sown area, net irrigated area and pesticides to be statistically significant inputs.~Originality / value of the article: This study contributes significantly to the literature on efficiency measurement of agricultural production in India by focussing on efficiency measurement of food grains. Most studies focus on farm level data and /or on individual crops.Implications of the research: This results of this study have implications for the issue of food security in India. Its results indicate that a need to expand irrigation facilities and net sown area to improve efficiency in food grain production which is vital for the issue of food security.
Keywords: C6; Q18; 330; food grains production; food security